TANGGUNG JAWAB PEMERINTAH TERHADAP PENGENTASAN KEMISKINAN (TINJAUAN EKONOMI ISLAM) - Umaima, Umaima (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2014)
Responsibility Against Government Poverty Reduction (Islamic Economic Outlook). In an Islamic economy, the government's responsibility is not only limited to the internal security and security systems from outside attacks, but also accountability in the program to achieve an ideal society; prosperous and fair. Through some literature, this paper raised how important the role of government in the economy, which is based on problems of poverty reduction. And finally came to the conclusion that the point is still the gap is so wide between the rich and the poor, the most responsible and will be held accountable at the same time is the future of government